The control of television content by the regulatory authorities and audiovisual councils - Aguaded-Gómez, José Ignacio (2009)
This work is a synthesis of the origins of these audiovisual regulatory authorities, analysing their regulatory functions and responsibilities regarding control of content. It also reflects on the actions taken by Audiovisual Control Boards as a result of their analysis of content and the problems arising from these analyses, along with their instruments of control: sanctions, recommendations, instructions…to conclude that free and independent societies need these boards to exist as a means of channelling their demands against the abuses of the media, and as elements that protect the most vulnerable sectors of those societies.